A Joint Optimization Criterion for Blind DS-CDMA Detection. (7th September 2006) - Durán-Díaz Durán-Díaz, Iván Iván; Cruces-Alvarez Cruces-Alvarez, Sergio A. Sergio A.
Abstract : This paper addresses the problem of the blind detection of a desired user in an asynchronous DS-CDMA communications system with multipath propagation channels. Starting from the inverse filter criterion introduced by Tugnait and Li in 2001, we propose to tackle the problem in the context of the blind signal extraction methods for ICA. In order to improve the performance of the detector, we present a criterion based on the joint optimization of several higher-order statistics of the outputs. An algorithm that optimizes the proposed criterion is described, and its improved performance and robustness with respect to the near-far problem are corroborated through simulations. Additionally, a simulation using measurements on a real software-radio platform at 5 GHz has also been performed.